Factors that interfere with prenatal care for pregnant adolescents (Research, Society and Development, 2020)
The objective was to describe the factors that interfere in the prenatal care of pregnant adolescents evidenced in scientific publications. An integrative literature review study was carried out by searching the LILACS and SciELO databases via VHL and PubMed. The following descriptors "Pregnancy", "Teen pregnancy", "Prenatal care", "Adolescent" and "Nursing care" were used together with the Boolean operator "AND". In total, 5,619 articles were found, of which, applied the inclusion criteria, 713 were selected for reading the titles and abstract. After careful reading, 13 articles were selected that met the research objective to compose the work. The results of the study showed the factors that interfere in the prenatal care of pregnant adolescents, with fear, insecurity, low income and low education as the main variables. In addition, the study also exposed the problems related to contraception and the causes that lead adolescents to not use it correctly. It was concluded that there is a need for improvement in the way health professionals approach the community in relation to adolescent sexuality, pregnancy and its prevention. Regarding prenatal care, we highlight that health professionals, especially nurses from the Family Health Strategy, have greater attention in relation to the active search of pregnant adolescents in their area and in carrying out education practices in health for pregnancy prevention in this group.